2017
DOI: 10.1093/pubmed/fdx133
|View full text |Cite
|
Sign up to set email alerts
|

Who uses foodbanks and why? Exploring the impact of financial strain and adverse life events on food insecurity

Abstract: Benefit-related problems appear to be a key reason for foodbank referral. By comparison with other disadvantaged groups, foodbank users experienced more financial strain, adverse life events, both increased the severity of food insecurity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
47
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(55 citation statements)
references
References 23 publications
(25 reference statements)
5
47
1
Order By: Relevance
“…A recent study of people using food banks in inner London reported similar socio‐demographic and financial characteristics (Prayogo et al . ).…”
Section: Who Is Receiving Help From Food Banks In the Uk?mentioning
confidence: 97%
See 2 more Smart Citations
“…A recent study of people using food banks in inner London reported similar socio‐demographic and financial characteristics (Prayogo et al . ).…”
Section: Who Is Receiving Help From Food Banks In the Uk?mentioning
confidence: 97%
“…About 15% of respondents were not born in the UK, generally matching the population of the UK, and <5% were asylum seekers. A recent study of people using food banks in inner London reported similar socio-demographic and financial characteristics (Prayogo et al 2017).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…We observed that FI was more likely in participants who reported difficulty making ends meet. Unemployment and delayed social benefit payments are frequently cited reasons for using food banks (26) . However, FI is not just a problem among unemployed individuals, as 76 % of the food insecure adults in our sample reported being employed.…”
Section: Interpretation Of Findings and Implications For Policymentioning
confidence: 99%
“…Thus, food bank usage is likely to underestimate the prevalence of FI (25) . Further, food bank users have been found to experience more financial strain and adverse life events, compared to other disadvantaged groups in which FI is prevalent (26) , meaning that users may not be representative of all those experiencing FI.…”
mentioning
confidence: 99%